Corrigendum to: A new OFRMPC formulation with on-line synthesis of the dynamic output feedback controller: A NEW OFRMPC FORMULATION WITH ON-LINE DOFC SYNTHESIS (International Journal of Robust and Nonlinear Control, (2017), 10.1002/rnc.3772) - Colombo Junior, José Roberto; Galvão, Roberto Kawakami Harrop; Assunção, Edvaldo [UNESP] (Wiley, 2021)
In the paper under consideration,1 Remark 6 should be corrected as follows. Equation (99) must be replaced with 106 (Formula presented.) The term (Formula presented.) in (101), (102), and (104) must be replaced with 107 (Formula presented.) which is similar to the (Formula presented.) matrix found in previous work.2 Accordingly, (Formula presented.) is defined as 108 (Formula presented.) where (Formula presented.) and (Formula presented.) correspond to the first (Formula presented.) lines of matrix (Formula presented.), and (Formula presented.), (Formula presented.) are additional matrix variables. The authors apologize for the mistakes. ACKNOWLEDGMENTS Roberto Kawakami Harrop Galvão and Edvaldo Assunção acknowledge the support of Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq, Brazil) under grants 303393/2018-1 and 301227/2017-9 (Research Fellowships). DATA AVAILABILITY STATEMENT Data sharing is not applicable to this article as no datasets were generated or analyzed during the current study. DATA AVAILABILITY STATEMENT Data sharing is not applicable to this article as no datasets were generated or analyzed during the current study.